Global ageing and labour potential employees of older age groups - Krypeichenko Ольга E. (Journal of the Belarusian State University. Economics, 2018)
The article considers one of the key trends and challenges of our time – the global aging of the population, which was the result of a decrease in fertility and increase in life expectancy, and has an impact on the prospects of world development. A comprehensive analysis of its impact on labour markets, both negative and opening up new opportunities, is being carried out. The current state policy can contribute to the processes of adaptation of society to demographic changes, or on the contrary complicate them, various options for its implementation are proposed. Under the concept of active ageing, older persons act as an economic and social resources.